Qingda granule inhibits angiotensin Ⅱ induced VSMCs proliferation through MAPK and PI3K/AKT pathways. (10th August 2020) - Yu, Na; Shen, Aling; Chu, Jianfeng; Huang, Yue; Zhang, Ling; Lin, Shan; Cai, Qiaoyan; Sankararaman, Senthilkumar; Sferra, Thomas J.; Chen, Youqin; Peng, Jun
Abstract: Ethnopharmacological relevance: The abnormal increase in vascular smooth muscle cell (VSMC) proliferation is widely accepted as the pivotal process in the vascular remodeling of hypertension. Qingda granule (QDG) is simplified from Qingxuan Jiangya Decoction (QXJYD) which has been in usage for a long time as a traditional Chinese medicine formula to treat hypertension based on the theory of traditional Chinese medicine. However, its underlying molecular mechanisms of action remain largely unknown. Aim of study: To investigate the therapeutic efficacy of QDG in the attenuation of elevation of blood pressure and proliferation of VSMCs in vivo and in vitro and explore its possible mechanism of action. Materials and methods: In vivo, we established an angiotensin Ⅱ (Ang Ⅱ)-mediated hypertension model in C57BL/6 mice and orally administered 1.145 g/kg/day of QDG. The systolic and diastolic blood pressures of all mice were measured at the end of the treatment by using the tail-cuff plethysmograph method and CODA™ noninvasive blood pressure system. VSMC proliferation within the aorta was determined by immunohistochemistry. In vitro, primary rat VSMCs were cultured to further verify the effects of QDG on Ang Ⅱ induced VSMC proliferation. Cell proliferation was investigated using cell counting and MTT assays. The protein expression was determined by western blotting. Results: We found that oral administration of QDG significantly attenuated the elevation of blood pressure and proliferation of VSMCs in Ang Ⅱ-induced hypertensive mice. Moreover, QDG remarkably inhibited Ang Ⅱ-induced primary rat VSMCs proliferation and decreased mitogen-activated protein kinase (MAPK) and PI3K/AKT activity by attenuating the expression of phospho-extracellular signaling-regulated kinase 1/2, phospho-p38, phospho-c-Jun N-terminal kinase and phospho-protein kinase B. Conclusion: Collectively, our findings suggest that QDG attenuates Ang Ⅱ-induced elevation of blood pressure and proliferation of VSMCs through a decrease in the activation of MAPK and PI3K/AKT pathways. Based on this study, we postulate this could be one of the mechanisms whereby QDG effectively controls hypertension. Graphical abstract: Image 1